Topical Steroid Withdrawal in Atopic Dermatitis: Patient-reported Characterization from a Swedish Social Media Questionnaire - Mikael Alsterholm; Maja af Klinteberg; Sophie Vrang; Gunnthorunn Sigurdardottir; MariHelen Sandström Falk; Alexander Shayesteh (Acta Dermato-Venereologica)
Topical steroid withdrawal (TSW) is described as an adverse reaction to topical glucocorticoids (TGCs). A pathophysiological mechanism has not been identified. There are no diagnostic criteria. The aim was to describe patient-reported characteristics of TSW in atopic dermatitis (AD). An observational cross-sectional study was performed by posting a questionnaire for participants, aged ≥18 years, reporting both AD and TSW, in a Swedish TSW-themed Facebook group during 4 weeks in 2023. The questionnaire was accessed by 98 participants, with 82 completing it. Most were female (95%), 18–39 years old (74%), self-diagnosed with TSW (84%), and reported current symptoms of AD and TSW. They defined TSW as dependency on TGCs and adverse reactions to their use. Erythema, desquamation, dryness, and oozing affecting the face, neck, and upper extremities were the most reported signs. Pruritus, sleep disturbance, and signs of anxiety and depression were the most reported symptoms. Recurring episodes of manifestations attributed to TSW were reported by 60%. The personal trigger factor was believed to be TGCs by 93%, and 33% also identified oral glucocorticoids. TGCs were currently used by 21%. Self-reported manifestations of TSW are similar to those of AD but appeared to be distinguishable for the participants and caused considerable morbidity.